PEMILIHAN BAHASA DALAM CERAMAH AGAMA ISLAM DI TEMBILAHAN, RIAU - Amalia Nazla Saldina; Suhandano Suhandano (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Tembilahan is the capital of the Indragiri Hilir regency in Riau and is nicknamed a worship city because of the Islamic influence brought by the ulama from South Borneo. Its community consists of various ethnic groups, such as Banjar, Malay, Buginese, Javanese, Minangkabau, and others, with the majority adherents of Islam. This diversity raises problems regarding the choice of language in the religious setting. This paper examines language choice patterns and the factors that determine the choice of languages. The data are drawn by using document analysis and the introspection method. The ethnography of communication approach was used to analyze the data. It reveals that five languages were used (Indonesian, Arabic, Banjar, Riau Malay Coastal dialect, and Javanese) by applying code-switching and code-mixing, thus forming nine patterns of language choice. The factors that determine the choice of those languages are ethnic and language background, the speaker's language competence, the speech's situation, and the speaker's purposes. The purposes of language choice are to emphasize, teach, respect, give an example, pray, quote Al-Quran and Hadith, praise Allah, quote others' statements, and humour. The conclusion is Banjar language is used as the dominant language. Even though there is still no found language use with a single variation in the Islamic sermons in Tembilahan, it shows that the Tembilahan community is classified as a multilingual society that can use more than one language.